Removal of microplastics by algal biomass from aqueous solutions: performance, optimization, and modeling - Fatemeh Lotfigolsefidi; Mojtaba Davoudi; Maryam Sarkhosh; Ziaeddin Bonyadi (Scientific Reports)
Abstract Microplastics (MPs) are emerging pollutants that pose significant risks to ecosystems due to their inherent toxicity, capacity to accumulate various pollutants, and potential for synergistic impacts. Given these concerns, the focus of this research is on the critical need for effective MPs removal from aquatic environments. Using BBD method, this study aimed to identify the key parameters affecting the removal of MPs by algal biomass from aqueous solutions. The investigation specifically analyzed the effects of varying initial PS concentrations (100 to 900 mg/L), pH values (4 to 10), reaction durations (20 to 40 min), and C. vulgaris dosages (50 to 400 mg/L). Data analysis indicated that QM best described the experimental findings, leading to the identification of optimal conditions for PS removal: a pH of 7.5, a reaction time of 31.90 min, a C. vulgaris dosage of 274.05 mg/L, and a PS level of 789.37 mg/L. Under these conditions, the study achieved a maximum removal efficiency of 73.01% for PS. These outcomes demonstrate the significant potential of C. vulgaris in efficiently removing PS from water. Furthermore, using algae as a green, eco-friendly alternative to conventional chemical coagulants offers a practical and sustainable approach to addressing MPs pollution in our water systems.